An assessment of mechanical properties of P92 steel weld joint and simulated heat affected zones by ball indentation technique. (3rd September 2018) - Barbadikar, Dipika R.; Sakthivel, T.; Ballal, A. R.; Peshwe, D. R.; Syamala Rao, P.; Mathew, M. D.
ABSTRACT: Mechanical properties of P92 steel weld joint fabricated by shielded metal arc welding were evaluated using ball indentation (BI) technique. Microstructure of the P92 weld joint consisted of the weld metal, coarse grain region, fine grain region, intercritical region and base metal. The individual microstructural regions of the heat affected zones (HAZs) were separately prepared by heat treating the steel at particular temperatures. Ball indentation and uniaxial tensile tests were carried out across the weld joint and on the simulated HAZ microstructures at temperatures of 300 K (27 °C) and 623 K (350 °C). The tensile strengths gradually decreased from weld metal to the base metal with trough in the intercritical region (ICR) of the joint and simulated at 1173 K (900 °C) steel. The formation of coarser M23 C6 precipitates and sub-grain formation with reduced dislocation density led to soften the ICR/simulated at 1173 K (900 °C) steel than the other regions of the joint. The variation of mechanical properties across the joint was comparable with variation of hardness and microstructural constituents across the joint.